New aporphine alkaloids from the aerial parts of Piper semiimmersum§. Issue 8 (3rd August 2018) - Zhang, Dong-Dong; Yang, Jun; Luo, Ji-Feng; Li, Xiao-Nian; Long, Chun-Lin; Wang, Yue-Hu
Abstract: Two new aporphine alkaloids, semiimmersumines A (1 ) and B (2 ), along with 20 known compounds, were isolated from the aerial parts of Piper semiimmersum (Piperaceae). The structures of the new compounds were elucidated based on the analysis of 1D and 2D NMR, MS, and CD data. The absolute configuration of semiimmersumine A (1 ) was determined by single crystal X-ray diffraction analysis using anomalous dispersion with copper radiation. The effects of all compounds from the plant on rabbit platelet aggregation induced by thrombin (IIa) or PAF were also evaluated. Abstract :